Gendered business models for improved cattle artificial insemination service delivery in Vietnam: IPSR Innovation Profile - Marshall, Karen; Burkart, Stefan; Thinh Nguyen; Bravo, Aura (2022)
Gender-sensitive business models for artificial insemination service providers for cattle in Vietnam, with a focus on economic performance and social responsibility.